Propriedades eletrônicas de grafeno com defeitos - Bueno, Maria Jannaira (2011)
In the limit of low energy, graphene can be described by a theory of free massless Fermions. In this work, we write a non-Euclidean metric that represents graphene and introduce a non-Abelian gauge field due to the presence of topological defects (disclinations). Furthermore, in this background, we study the elastic scattering of Fermions by these defects. Afterwards, we obtain the phase shift angle and the scattering amplitude. We also discuss the influence of these results to transport properties. In this approach, we apply a uniform magnetic field perpendicular to the graphene sheet. Thus, the system also becomes described by an Abelian gauge field and we observe that occurs the break of the degeneracy of Landau levels with possible physical implications for the study of the quantum Hall effect in graphene. In addition, we study the dynamics of Dirac spinors in the presence of a confining potential, as the Dirac oscillator, and the spatial confinement of electrons in a graphene structure in the shape of a ring with topological defects. Finally, we find that the dynamics of spinors is affected by this geometry and the disclination.